Performance analysis of the cdma2000 reverse packet data channel. (6th January 2009) - Basyouni, Ayda; Agarwal, Anjali; Elhakeem, Ahmed
As wireless data networks are becoming an essential element in our daily life, service providers are struggling to fulfill the high data rate requirements to support wireless data applications. cdma2000 1xEV-DV, developed by the third generation partnership project 2 (3GPP2), is one of the latest standards promising to fulfill the high data rate requirements of the third generation wireless technologies. In this paper, the performance of cdma2000 1xEV-DV reverse packet data channel is investigated. In particular, based on the properties of the 1xEV-DV turbo encoder, lower bounds on the probabilities of data sub-packets acceptance are derived. Using these probabilities, expressions for the expected file transmission time and effective data rate are obtained for both the error-free and noisy acknowledgement channels.